Triglyceride-Glucose Index and its Relationship to Erectile Dysfunction in Subjects without Heart Disease - Sudeep Jayaram; S Santhosh; Nikhil Vaidya; Arifa Bakerywala; Harsh Anadkat; Heena Shaikh (Journal of Pharmacy and Bioallied Sciences)
Aim: This study primarily focused on evaluating the triglyceride-glucose (TyG) index in patients experiencing erectile dysfunction (ED) and examining its potential role as a predictive tool in diagnosing ED. Materials and Methods: The study involved a cohort of 50 patients diagnosed with erectile dysfunction, forming the study group, alongside 50 individuals exhibiting normal sexual function, who served as the control group. The assessment of erectile function was conducted using the International Index of Erectile Function-5 (IIEF-5) questionnaire. All participants underwent the calculation of the TyG index. Results: The examination indicated that there were no notable disparities between the two groups regarding smoking rates, alcohol intake, or measurements of high-density lipoprotein cholesterol, haemoglobin, creatinine levels, and leukocyte and platelet counts. Individuals experiencing erectile dysfunction were found to be older and exhibited significantly higher levels of total cholesterol, low-density lipoprotein cholesterol, glucose, triglycerides, and the TyG index compared to the control group. Conclusion: I n patients with erectile dysfunction, the TyG index—a simple test for insulin resistance (IR) —was found to be predictive.